Behind anti-corruption, the transformations of society—investigation into the politicization of “illegal personal enrichment” in Romania - Oprea, Alexandra (Frontiers in Political Science, 2024)
This article adopts a Durkheimian perspective and employs a socio-pragmatic method of inquiry, with a specific focus on analyzing “scandals” as critical junctures and the interpretations provided by social actors. The aim is to explore the development of corruption as a social issue in Romania over the past four decades. In contrast to two prevailing explanatory approaches in Romania, labeled here as fatalistic and voluntarist, we propose a more reflective approach. This perspective illustrates how the increasing division of labor and the subsequent rise in individualization within social relations have progressively influenced the tendencies and sensitivities of various social groups in Romanian society, particularly regarding what this study refers to as “illegal personal enrichment” (IPE). By focusing on discourse analysis of debates on corruption, this study analyses the evolution of the politicization of corruption—a subject still largely unexplored but highly prevalent in the public sphere—in conjunction with the structural changes in Romanian society. Consequently, three stages can be identified: IPE as a discursive tool for denouncing political adversaries, IEP as a generator of political conflicts, and IEP as a public issue.